An attachment-based model of therapeutic change processes in the treatment of personality disorder among male forensic inpatients - Willmot, Phil (Legal and criminological psychology, 2016)
Purpose. This study explores the processes of change during treatment among male forensic inpatients with primary diagnoses of personality disorder. Method. Fifty patients in a high secure personality disorder treatment service completed a checklist about how they had changed during treatment and the factors that had caused that change. Results. The results support a limited reparenting attachment-based model of therapeutic change. Self-reported levels of change were highly correlated with measures of patient functioning, though significant levels of change did not occur until the later stages of treatment. Conclusions. The behaviour of therapists was particularly important throughout treatment, though participants in the final stage of therapy reported that the behaviour of other staff was as important as that of therapists, suggesting that, by this stage of treatment they are able to extend their range of supportive and therapeutic relationships.